Hubungan Penyakit Periodontal pada Ibu Hamil dengan Kejadian Bayi Berat Badan Lahir Rendah (BBLR) - Baliung, Ratika F.; Wowor, Vonny N. S.; Khoman, Johanna A. (e-GiGi, 2021)
Abstract: Periodontal disease is still one of the dental and oral health disorders that has a high prevalence worldwide. Moreover, it can cause disorders in pregnancy including low birth weight (LBW) infant with the risks of death as well as disorders of growth and development in children. To date, low birth weight is one of the causes of high infant mortality rate. This study was aimed to evaluate the relationship between periodontal disease in pregnant women and the incidence of LBW baby. This was a literature review study searching data on three databases namely Pubmed, ScienceDirect, and Google Scholar and using keywords and a combination of boolean operators. After being selected based on inclusion and exclusion criteria, critical appraisal was conducted, and nine literatures were obtained: cross sectional study, case-control study, cohort study designs. The results showed that the most common periodontal disease in pregnant women was periodontitis. Women who gave birth to LBW babies had poor periodontal conditions compared to women who gave birth to babies with normal weight. Most of the literatures showed a significant relationship between periodontal disease in pregnant women and the incidence of LBW baby. In conclusion, there is a relationship between periodontal disease in pregnant women and the incidence of LBW infant. Periodontitis is one of the risk factors of poor pregnancy outcomes.Keywords: periodontal disease; pregnant women; low birth weight (LBW)Â Â Abstrak: Penyakit periodontal masih merupakan salah satu gangguan kesehatan gigi dan mulut dengan prevalensi cukup tinggi di dunia. Dampak penyakit periodontal dapat berupa gangguan pada kehamilan termasuk terjadinya kelahiran bayi berat badan lahir rendah (BBLR) yang berisiko kematian bayi, serta gangguan pertumbuhan dan perkembangan anak. Bayi BBLR merupakan salah satu penyebab tingginya angka kematian bayi (AKB). Penelitian ini bertujuan untuk mengetahui hubungan antara penyakit periodontal pada ibu hamil dengan BBLR. Jenis penelitian ialah suatu literature review dengan pencarian data pada tiga database yaitu Pubmed, ScienceDirect, dan Google Scholar menggunakan kata kunci dan kombinasi boolean operator. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi, dilakukan critical appraisal, dan didapatkan sembilan literatur dengan desain studi cross sectional, case-control, dan cohort. Hasil penelitian mendapatkan bahwa penyakit periodontal yang terbanyak pada ibu hamil ialah periodontitis. Ibu yang melahirkan bayi BBLR memiliki kondisi periodontal yang buruk dibandingkan ibu yang melahirkan bayi dengan berat badan cukup. Sebagian besar literatur yang ditelaah menunjukkan adanya hubungan bermakna antara penyakit periodontal pada ibu hamil dengan kejadian BBLR. Simpulan penelitian ini ialah terdapat hubungan bermakna antara penyakit periodontal pada ibu hamil dengan kejadian bayi BBLR. Periodontitis merupakan salah satu faktor risiko hasil kehamilan yang buruk.Kata kunci: penyakit periodontal; ibu hamil; berat badan lahir rendah (BBLR)